Sorgner, S. L. (2021). We have always been cyborgs: digital data, gene technologies, and an ethics of transhumanism. - Stamati, Ioanna - Maria (Journal of Posthumanism, 2023)
The monograph We Have Always Been Cyborgs: Digital Data, Gene Technologies, and an Ethics of Transhumanism by Stefan Lorenz Sorgner aims to explain the most critical issues the Transhumanistic field has been dealing with, including gene technologies, cyborg technologies, gene-motivational technics, gene ethics, mind uploading, policy-making, the image and identity of the Transhuman community.